Unemployment issues and problems in Kinta, Manjung and Kuala Kangsar, Perak, Malaysia - Mohamed Osman, Mariana; Bachok, Syahriah; Muslim, Siti Aisyah; M Bakri, Nurul Izzati (Elsevier, 2015)
Unemployment is one of the macroeconomic problems that signal the inefficient use of capital resource in the market. The research on unemployment in the Districts of Kinta, Manjung and Kuala Kangsar in Perak aims to identify the issues and problems related to the unemployment. A survey on 203 of respondents conducted randomly was to assess the current socio-economic condition of unemployment. Issues identified such as mismatched in location of work and availability of workers and increase of foreign worker in the local labor market. Hence, several recommendations proposed to overcome the issues of unemployment in the study.